Cytotoxicity mechanism of gallic acid and methyl gallate combined with cisplatin on cervical cancer (HeLa) cells - Mamat, Norlida (2025)
Cervical cancer is the fourth most common cause of cancer-related death affecting women worldwide. Cisplatin is one of the chemotherapy drugs used in the treatment of cervical cancer. However, cisplatin was reported to cause toxicity to normal cells and develop cell resistance with other side effects. Combining chemotherapy agents is one of the strategies to increase the effectiveness of anticancer drugs through synergistic effects. Gallic acid and methyl gallate are the most abundant phenolic compounds that have been reported to have good antioxidant and anticancer activities. Hence, in this study, gallic acid and methyl gallate were selected as combination substances with cisplatin. This study was conducted to elucidate the cytotoxicity mechanism of gallic acid and methyl gallate combined with cisplatin on cervical cancer (HeLa) cells through apoptosis mode of cell death. Furthermore, the antioxidant capacity of the cells treated with single and combination treatment was also evaluated. Cytotoxicity activity of gallic acid, methyl gallate and cisplatin on HeLa and NIH/ 3T3 cells was determined using MTT assay. The effects of gallic acid and methyl gallate combined with cisplatin were then determined using CompuSyn software. The morphology and percentage of apoptotic cells were evaluated using Hoechst staining and annexin V/PI assay. The expression of apoptotic and anti-apoptotic proteins (Bax, Bcl-2, caspase-3, caspase-9 and p53) was further determined by western blot analysis. The migration inhibitory effect of the combinations was also evaluated using scratch wound healing assay. The antioxidant activity of gallic acid and methyl gallate was measured using DPPH assay. Reactive oxygen species (ROS) and antioxidant enzyme activity were measured spectrophotometrically while the expression of antioxidant genes (SOD1 and hCAT) in HeLa-treated cells was then evaluated using RT-PCR. Gallic acid and methyl gallate showed strong cytotoxicity effects on HeLa cells. The IC50 values of gallic acid, methyl gallate and cisplatin on HeLa cells were 13.44 μg/mL, 16.55 μg/mL and 8.04 μg/mL whereas in NIH/3T3 cells were 32.90 μg/mL, 35.70 μg/mL and 6.57 μg/mL respectively. Gallic acid and methyl gallate in combination with cisplatin inhibited greater HeLa cell proliferation than cisplatin alone with synergistic effects seen in combination with cisplatin at concentrations of 0.51-4.02 μg/mL. Morphological observation of Hoechst staining then revealed the appearance of several apoptotic features in all treated cells. Consistently, flowcytometry analysis showed that the percentages of early apoptotic cells in the combination of cisplatin-gallic acid (28.72 ± 1.14) and cisplatin-methyl gallate (23.37 ± 9.72) groups were significantly higher than the control group (6.00 ± 0.95). The combination treatments significantly upregulated Bax, caspase-3, caspase-9 and p53 expressions and downregulated bcl-2 expressions as compared to the untreated group. Moreover, the treatments were shown to have migration-inhibitory effects after 24 hours. Gallic acid and methyl gallate exhibited strong antioxidant activity with EC50 values of 18.23 μM and 19.39 μM respectively. The combination treatments significantly increased intracellular ROS levels and reduced the level of SOD and catalase in an enzymatic assay. This result was consistent with RT-PCR result that showed the downregulation of SOD1 and hCAT genes in all treated samples. In conclusion, these findings suggest that the combination of gallic acid and methyl gallate with cisplatin synergistically inhibited proliferation by inducing apoptosis and ROS in cervical cancer cells